How does Congress work? - Small, Cathleen (Small, Cathleen. American democracy in action., 2019)
Provides a history of the United States Congress and discusses the mandates and work they are tasked with. Includes color images, a visual summary of how bills are turned into laws, a glossary, sources for further information, and an index.